Exploring the Impact of Generative AI on UX Design: Understanding the Dynamics of AI Integration - Widenborg,Emil; Dageson,Ludvig (2024)
This thesis examines the integration and impact of Generative AI (GenAI) on UX design, emphasizing human-AI collaboration and task complexity. Utilizing AI Sensemaking and Actor-network Theory (ANT), the study reveals that GenAI tools have transitioned from experimental aids to essential components in the design process, significantly enhancing productivity, particularly in prototyping and idea generation. Human designers retain creative and decision-making control, using AI as a supportive tool, especially for simpler tasks, while complex tasks necessitate more human oversight. The interaction between designers, GenAI tools, organizational policies, and stakeholders is crucial, with positive attitudes towards AI enhancing its benefits and data privacy concerns limiting its use. Challenges include the need for precise prompting, potential biases, and data privacy issues, with future improvements in GenAI tools expected to enhance reliability, context understanding, and integration capabilities. The thesis underscores the importance of maintaining human oversight to maximize the benefits of GenAI in UX design, recommending continued exploration and support for AI integration through training and clear policies. Future research should investigate the long-term impact of GenAI on UX roles as well as broader societal implications.
Keywords: AI; GenAI; Generative AI; Human-AI Collaboration; UX